#TITLE_ALTERNATIVE# - SYANJAYA (NIM : 10206036); Agung Nugroho, IRFAN
Lithium Vanadate (LiV2O4) is a transition metal oxides material which has large electronic heat capacity coefficient value then LiV2O4 could be classified as heavy fermion material. Increasing of heat capacity coefficient value for that compound is because present of electronic correlation effect, which is still interesting topic to be studied, because of electronic correlation effect in metal compounds cause for increasing electron localization effect. In this final project, electron correlation aspect in LiV2O4 compound will be studied based on electronic structure calculation using density functional theory (DFT) method. In the calculation scheme is used projector augmented wave (PAW) basis and local density approximation (LDA) for calculation of exchange-correlation effect. The whole calculation is done with using ABINIT program. Some of LDA method will be used and analyzed to get suitable electron correlation form for electronic heat capacity coefficient value of LiV2O4.